RETRACTED: How maritime logistic SMEs lead and gain competitive advantage by applying information technology? - Luo, Dean; Shahbaz, Muhammad Saeed; Qureshi, Muhammad Asif; Anis, Maira; Mahboob, Farhan; Kazouz, Hayfa; Mao, Jie (Frontiers in Psychology, 2022)
The aim of this study is to examine the importance of information technology for logistic SME’s of Pakistan. It is the time of technological rapidness especially after COVID-19 the word business has majorly transform to digital business. If an organization did not shift toward technology, it will be hard for it to even sustain in this rapid era. This study adopts the questionnaire after extensive literature review. It is quantitative study a survey was conducted among logistics SME’s of Pakistan to empirically verify that what competitive advantages they are leading and gaining from information technology and how much information technology is important for their sustainability. The literature lacks information about the ways in which Information Technology has been integrated in logistics SME’s operating and more specifically there is no information about IT valence, IT resource commitment, IT managerial commitment, and IT competency. The research is primary quantitative in nature, where the data was collected via close-ended questionnaire from 340 logistics SME’s of Pakistan. The independent variable of this research was Information Technology (i.e., IT valence, IT resource commitment, IT managerial commitment, and IT competency); whereas the dependent variable was competitive advantage. The study found that IT had significant impact on competitive advantage of logistics SME’s operating in Pakistan. All the variables related to IT had significant impact on competitive advantage, which included; IT valence, IT resource commitment, IT managerial commitment, and IT competency. This study will help manages and owners of logistic SME’s in decision making. They can understand how much IT can enhance their performance and reduce the risks. This research has specifically been conducted with logistics SME’s operating in Pakistan, which means that there is much scope to be worked upon i.e., by selecting companies operating in other countries, and compare with current findings. This research study the impact Information technology (I IT valence, IT resource commitment, IT managerial commitment, and IT competency) on competitive advantage, others independent variables can be study to find the impact on competitive advantage.